The relationship of teaching, social and cognitive presence with course satisfaction in a TESL programme course in a public university in Sabah, East Malaysia - Tan, Choon Keong (Scholink Inc., 2021)
The purpose of this study was to examine whether teaching presence, social presence and cognitive presence were significant predictors of course satisfaction in a blended learning course at a public university in Sabah, East Malaysia. The research design was based on the Community of Inquiry framework survey involving 32 third-year undergraduates majoring in TESL (Teaching of English as a Second Language). Pearson r correlational analysis was used to determine the relationship between teaching presence, social presence, cognitive presence and course satisfaction. The findings of this study showed that both social presence and cognitive presence were significantly associated with course satisfaction, but not with teaching presence.